Management of Coronavirus Disease 2019 Intubation Teams. Issue 8 (June 2020) - Patel, Gaurav P.; Collins, Jeremy S.; Sullivan, Cinnamon L.; Winters, Bradford D.; Pustavoitau, Aliaksei; Margulies, Susan S.; Lynde, Grant C.
Abstract : Some patients infected with the Coronavirus Disease 2019 (COVID-19) require endotracheal intubation, an aerosol-generating procedure that is believed to result in viral transmission to personnel performing the procedure. Additionally, donning and doffing personal protective equipment can be time consuming. In particular, doffing requires strict protocol adherence to avoid exposure. We describe the Emory Healthcare intubation team approach during the COVID-19 pandemic. This structure resulted in only 1 team member testing positive for COVID-19 despite 253 patient intubations over a 6-week period with 153 anesthesia providers on service.